The Impact Of Level Of Resistance And Gender On Influence Tactics - Kuan, Huai Ly (2004)
Using power-influence leadership theory, this study sought to test the relationship between user’s level of resistance and change agents’ use of influence tactics during the new technology or information system implementation. Impacts of gender of the user, gender of the change agent, and the interaction among variables on the use of influence tactics were also examined.